On Mules and Bodies: Black Captivities in the Brazilian Racial Democracy (2014)
This article situates the past decade's boom in Brazil's prison population in the context of the country's enduring system of racial domination. Prison demographics are analyzed in relation to the role that race and gender play in configuring both the regime of legality' and contemporary urban war against particular territories and bodies in Brazil. The article also pays close attention to gendered captivities of disenfranchised black women trapped as 'mules' in the underground drug economy. Ethnographic fieldwork in a SAo Paulo women's prison provides the basis for a critique of the regime of punishment that structures black lives in the neoliberal city.